Physicochemical studies of galvanized steel corrosion in urban, industrial, and marine environments, and corrosion mapping of Karachi city: An important coastal city of the 21st‐century modern maritime silk route. Issue 12 (22nd July 2020) - Zafar, Faiza; Bano, Humaira; Mahmood, Azhar; Corvo, Francisco; Rodriguez, Joelis
Abstract: The coastal city of Karachi is an imperative part of China–Pakistan Economic Corridor, which is integrated with the modern maritime silk route of the 21st century. This paper presents the corrosion mapping and physicochemical studies of galvanized steel corrosion exposed at the urban, industrial, and marine test sites located in the Karachi coastal city from July 2018 to June 2019. Tests have been performed to determine chloride, sulfur dioxide, time of wetness (TOW), and corrosion rates as per ISO protocols 9223 and 9225, and ASTM standards G1, G50, G140‐02, D4458‐94, and D2010. All test sites have been assigned the C5+ corrosivity category, based on corrosion rates of the galvanized steel, which is not completely in line with the corrosivity category derived from atmospheric pollutants and TOW values for these test sites. SEM/EDS, XRD, and FTIR have characterized the presence of simonkolleite, hydrozincite, and zincite at nearly all the test sites, whereas gordaite is only detected at the marine test sites. Zinc(I) chlorohydroxysulfate is also observed at an urban test site. This study has furnished a novel product of a galvanized steel corrosion map for Karachi, Pakistan. Abstract : This study has furnished a galvanized steel corrosion map for Karachi city, an important coastal city of the 21st‐century modern maritime silk route and a key part of China–Pakistan Economic Corridor, by employing ASTM and ISO standards that complement spectroscopic techniques.